TERAPI OKUPASI MENGGAMBAR TERHADAP PERUBAHAN TANDA DAN GEJALA HALUSINASI PADA PASIEN DENGAN GANGGUAN PRESEPSI SENSORI HALUSINASI DI RSUD TOMBULILATO - Firmawati Firmawati; Fadli Syamsuddin; Restivera Botutihe (Jurnal Medika Nusantara, 2023)
Hallucinations are a symptom of mental disorders in individuals characterized by changes in sensory perception: feeling false sensations in the form of sound, sight, touch, taste and smell. Patients with hallucinations get a response about their environment without any real object of stimulation. The purpose of this study was to determine Occupational Drawing Therapy for Changes in Signs and Symptoms of Hallucinations in Patients with Hallucination Sensory Perception Disorders at Tombulilato Hospital. Pre-experimental research design with one group pretest and posttest research design. Sampling using Total Sampling with 15 respondents. Data collection used an observation sheet with the results of the study that there were 15 (100%) respondents with severe hallucinations before being given occupational drawing therapy and after being given occupational drawing therapy there were 14 (93.0%) respondents with mild hallucinations and there was 1 (7.0%) ) respondents with severe hallucinations. The results of statistical tests using the Paired T-Test showed a p value = 0.000 with ? <0.05, there was a significant effect between occupational drawing therapy on changes in signs and symptoms in patients with hallucinatory sensory perception disorders. It is hoped that changes in signs and symptoms can reduce hallucinations from patients.